Book review: Advanced Introduction to Comparative Constitutional Law. - Ainhoa Martinez (Oñati Socio-Legal Series)
Tushnet presents a thoughtful introduction to the field of comparative constitutional law through a review of recent literature and an analysis of the key contemporary issues in constitutional design and structure. In the following lines a review of his book is presented.